Labored relations : law, politics, and the NLRB--a memoir - Gould, William B., IV (MIT Press, 2000)
Annotation "This book is about the relationship between law, a quasi-judicial administrative agency, and politics, in the volatile arena of labor policy and the balance of power between labor and management ... It is about the rule of law and the role of labor law in a modern economy."--The IntroductionFrom 1994 to 1998, William B. Gould IV served as Chairman of the National Labor Relations Board. One of only three NLRB Chairmen to come from an academic background, he quickly realized that he was an outsider in a very political world. In this compelling memoir, Gould describes the tribulations of trying to assure impartial administration of federal labor laws while faced with a hostile, Republican Congress. He describes his difficult confirmation process and wrenching Congressional hearings, particularly the one over Proposition 226, a ballot initiative that required unions to get explicit authorization from all represented workers prior to expending dues for political purposes. He tells how the behavior of both Board members and members of Congress, guided by self-interest and rigid ideology, contributed to the Board's problems. He also recounts the positive strides the NLRB made during his tenure, despite the turmoil. The book provides an insider's view of what goes on behind the closed doors in our nation's capital, including discussions with members of Congress, the White House, and President Bill Clinton